Statistics in psychology using R and SPSS - Rasch, Dieter; Kubinger, Klaus D. , 1949-; Yanagida, Takuya (John Wiley & Sons, 2011)
Statistics in Psychology covers all statistical methods needed in education and research in psychology. This book looks at research questions when planning data sampling, that is to design the intended study and to calculate the sample sizes in advance